An empirical nexus between oil price collapse and economic growth in Sub-Saharan African oil based economies - KEJI Sunday Anderu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The focus of this study, is to empirically investigate the nexus between oil price collapse and economic growth in sub-Saharan Africa oil based economies, specifically from Angola, Nigeria and Sudan between January, 2010 and December, 2015, through panel random effects model (REM): Economic growth rate (GDPR) and independent variables: Oil price (OPR), Exchange rate (EXR), Industrial Output (IND) and Terms of Trade (TOT. REM result showed that there is negative link between oil price collapse and the economic growth in the case of Angola, Nigeria and Sudan, which confirmed the nexus between oil price collapse and economic growth. Post estimation tests such as Hausman and Breusch and Pagan Lagrange Multiplier Test were adopted to empirically show the consistency and efficiency of the model. Interestingly, the two key variables (GDPR and OPR) disclose how unprecedented oil price fall disrupts economic growth of the selected economies. Meanwhile, poor institutional quality in the oil sector coupled with poor fiscal measure among others, further expose these economies to unprecedented external shocks that was characterized by skyrocket exchange rate, hence destabilize growth within the period under review. Therefore, the need for a robust fiscal measure is pertinent in order to sustain economic growth